Similar additive effects of doxorubicin in combination with photon or proton irradiation in soft tissue sarcoma models - Bernardo, Teresa; Behrends, Carina; Klein, Diana; Kuntze, Anna; Timmermann, Beate; von Neubeck, Cläre (Frontiers in Oncology, 2023)
High-precision radiotherapy with proton beams is frequently used in the management of aggressive soft tissue sarcoma (STS) and is often combined with doxorubicin (Dox), the first line chemotherapy for STS. However, current treatment approaches continue to result in high local recurrence rates often occurring within the treatment field. This strongly indicates the need of optimized treatment protocols taking the vast heterogeneity of STS into account thereby fostering personalized treatment approaches.Here we used preclinical STS models to investigate the radiation response following photon (X) or proton (H) radiation alone and in combination with different treatment schedules of Dox. As preclinical models, fibrosarcoma (HT-1080), undifferentiated pleiomorphic sarcoma (GCT), and embryonal rhabdomyosarcoma (RD) cell lines were used; the latter two are mutated for TP53. The cellular response regarding clonogenic survival, apoptosis, cell cycle distribution, proliferation, viability, and motility was investigated. The different STS cell types revealed a dose-dependent radiotherapy response with reduced survival, proliferation, viability, and motility while G2/M phase arrest as well as apoptosis were induced. RD cells showed the most radiosensitive phenotype; the linear quadratic model fit could not be applied. In combined treatment schedules, Dox showed the highest efficiency when applied after or before and after radiation; Dox treatment only before radiation was less efficient. GCT cells were the most chemoresistant cell line in this study most probably due to their TP53 mutation status. Interestingly, similar additive effects could be observed for X or H irradiation in combination with Dox treatment. However, the additive effects were determined more frequently for X than for H irradiation. Thus, further investigations are needed to specify alternative drug therapies that display superior efficacy when combined with H therapy.